Respuesta :

Space

Answer:

[tex]z=\frac{at-67}{45+a}[/tex]

Step-by-step explanation:

Step 1: Write out equation

a(t + z) = 45z + 67

Step 2: Distribute a

at + az = 45z + 67

Step 3: Subtract 67 on both sides

at + az - 67 = 45z

Step 4: Subtract az on both sides

at - 67 = 45z + az

Step 5: Factor out z

at - 67 = z(45 + a)

Step 6: Divide both sides by 45 + a

[tex]z=\frac{at-67}{45+a}[/tex]

Answer:

Step 1: Write out equation

a(t + z) = 45z + 67

Step 2: Distribute a

at + az = 45z + 67

Step 3: Subtract 67 on both sides

at + az - 67 = 45z

Step 4: Subtract az on both sides

at - 67 = 45z + az

Step 5: Factor out z

at - 67 = z(45 + a)

Step 6: Divide both sides by 45 + a

Step-by-step explanation: